2011
DOI: 10.2337/dc10-2303
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Type 2 Diabetes and Exposure to Persistent Organic Pollutants

Abstract: OBJECTIVEThe prevalence of type 2 diabetes is increasing alarmingly in both developed and developing countries. Recently, exposure to persistent organic pollutants (POPs) has been associated with the prevalence of type 2 diabetes. The purpose of this cross-sectional study is to examine the association between type 2 diabetes and POP exposure in the Helsinki Birth Cohort Study.RESEARCH DESIGN AND METHODSThe cohort consists of 8,760 people born in Helsinki during 1934–1944, before the global POP emission peak. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
96
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(109 citation statements)
references
References 25 publications
9
96
2
2
Order By: Relevance
“…Our study population included only middle-aged and older men, so the findings may not be generalizable to other age groups or to women. Besides mercury, we did not have information on other environmental contaminants in fish, such as persistent organic pollutants, which have been associated with insulin resistance and higher risk of type 2 diabetes (39,40). Of special interest would be to investigate the potential joint effects of simultaneous mercury and persistent organic pollutant exposures, of which very little is currently known (16).…”
Section: Discussionmentioning
confidence: 99%
“…Our study population included only middle-aged and older men, so the findings may not be generalizable to other age groups or to women. Besides mercury, we did not have information on other environmental contaminants in fish, such as persistent organic pollutants, which have been associated with insulin resistance and higher risk of type 2 diabetes (39,40). Of special interest would be to investigate the potential joint effects of simultaneous mercury and persistent organic pollutant exposures, of which very little is currently known (16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PCDD/Fs, polychlorinated biphenyls (PCBs), and methyl mercury (MeHg) are suspected to have a capacity to increase both blood pressure and oxidative stress, alter lipid, glucose and insulin metabolism, and promote inflammatory processes (Everett et al, 2011;Hennig et al, 2007;Mozaffarian, 2009). Especially exposure to PCBs has lately been linked with obesity, dyslipidemia, insulin resistance (Lee et al, 2011) and the risk of diabetes (Airaksinen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The main source of human exposure to p,p'-DDE is through eating food, particularly fish. Several cross-sectional studies have disclosed the association of POPs with T2D (Lee et al, 2006 ;Taylor et al, 2013 ;Airaksinen, Rantakokko, Eriksson, Blomstedt, & Kajantie, 2011;Mostafalou, 2016). Some limited prospective studies have also shown that POPs increased the risk of T2D (Arrebola, Pumarega, Gasull, Fernandez, & Martin-Olmedo, 2013;Rignell-Hydbom, Lidfeldt, Kiviranta, Rantakokko, & Samsioe, 2009;Turyk, Anderson, Knobeloch, Imm, & Persky, 2009), but the association between p,p'-DDE and T2D has not been specifically studied.…”
Section: Introductionmentioning
confidence: 99%